Enhancing Intermediate-Level Learners' Speaking Skills through Communicative Language Approach in Online Setting - Radchuk, Olha (Univerzita Pardubice, 2025)
This bachelor thesis explores whether the speaking skills of adult intermediate-level learners can be improved through the application of the Communicative Language Teaching (CLT) approach in a non-formal online setting. The paper is divided into two parts: theoretical and practical. The theoretical part compares formal and non-formal, online and face-to-face educational settings and thoroughly discusses the CLT approach. The practical part presents the implementation of these concepts in an online learning environment.
Rozvoj řečové dovednosti mluvení u středně pokročilých studentů prostřednictvím komunikačního přístupu v online prostředí
Keywords: non-formal English learning; Communicative Language Teaching (CLT); intermediate adult learners; online English teaching; neformální výuka angličtiny; komunikační přístup ve výuce angličtiny; středně pokročilí dospělí studenti; online výuka angličtiny